(untitled) (Indian Journal of Veterinary Pathology, 2025)
A twelve-year-old airport sniffer male Labrador dog was brought to Veterinary Clinical Complex, VCRI, Namakkal with the history of sudden seizures and drooling of saliva. However, the dog was found dead while on arrival at the Veterinary Clinical Complex. The dog carcass was referred to the Department of Veterinary Pathology, VCRI, Namakkal for necropsy. On gross examination, multiple blackish nodular growths in the oral cavity; leathery appearance of lungs with tiny raised greyish nodules; dark blackish raised nodules in spleen; shrunken kidneys with focal blackish areas in cortico-medullary junction; blackish discolouration with haemorrhage in intestine; thickened urinary bladder and prostate gland were observed. Cytological examination of oral growth revealed clusters of melanin-laden melanocytes with anisocytosis, anisokaryosis, prominent nucleoli and intracytoplasmic coarse granular melanin pigments. Histopathological examination of the oral growth exhibited replacement of normal stratified squamous epithelium with numerous melanin-laden melanocytes. In addition, melanin-laden melanocytes were also noticed in various organs like lungs, spleen, kidney and intestine. This case deals with oral melanoma with multicentric metastasis to various organs in a sniffer dog.